1993
DOI: 10.1111/j.1365-3059.1993.tb01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impacting rain drops on the growth and development of powdery mildew fungi

Abstract: The effects of rain on different stages of powdery mildew development were investigated quantitatively for Erysiphe graminis on barley, Erysiphe pisi on pea and Sphaerotheca pannosa on rose. Water drops 4 mm in diameter released from a height of 2 5 m onto target leaves reduced the numbers of conidia on the impacted surfaces and inhibited subsequent mildew development, the effects declining as the interval between inoculation and impaction increased. Simulated rainfall applied after inoculation reduced the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 6 publications
0
11
1
2
Order By: Relevance
“…Sivapalan (1993) demonstrated that rain can cause physical damage to mildews, and the correlation between rainfall and strawberry powdery mildew conidia was negative and significant (Blanco et al 2004). However, in our study, only 4 rainy days occurred in the 2007-2008 season when spores were trapped.…”
Section: Discussioncontrasting
confidence: 53%
“…Sivapalan (1993) demonstrated that rain can cause physical damage to mildews, and the correlation between rainfall and strawberry powdery mildew conidia was negative and significant (Blanco et al 2004). However, in our study, only 4 rainy days occurred in the 2007-2008 season when spores were trapped.…”
Section: Discussioncontrasting
confidence: 53%
“…Although mildew is common and causes considerable damage in cool areas; they are even more common and severe in areas with warm, dry climates, because in these conditions the wind easily detaches and spreads the conidia (RomeroCova, 1988); also, it has been established that mildew presents itself in the succulent tissue of the host in cool, shady areas (Yarwood, 1973). The lives of conidia are brief and they are favored by high relative humidity, but not by rain and inmersion in water (Sivapalan, 1993a;Sivapalan, 1993b). In general, the mycelium is epiphitic, except in genuses Leveillula, Phyllactinia, Pleochaeta where the mycelium is hemi-endophytic, and occasionally in species of Cystotheca; in this case, hyphae penetrate the leaves through the stomata and form mycelia inside, although the mycelia of the species of Leveillula are more abundant inside the leaf of the host (Braun et al, 2002).…”
Section: Palabras Clave Adicionalesmentioning
confidence: 99%
“…In con clima cálido y seco, porque en estas condiciones el viento fácilmente desprende y disemina los conidios (Romero-Cova, 1988); además se ha establecido que, las cenicillas se presentan en tejido suculento del hospedante en ambientes sombreados y frescos (Yarwood, 1973). La vida de los conidios es corta y les favorecen altos niveles de humedad relativa, pero no son favorecidos por lluvia e inmersión en agua (Sivapalan, 1993a;Sivapalan, 1993b). En general, el micelio es epifítico excepto en los géne-ros Leveillula, Phyllactinia, Pleochaeta el micelio es hemiendofítico y ocasionalmente en especies de Cystotheca; en este caso, las hifas penetran las hojas a través de los estomas y forman micelio en el interior, sin embargo, el micelio de las especies de Leveillula es más abundante en el interior de la hoja del hospedante (Braun et al, 2002).…”
Section: Palabras Clave Adicionalesunclassified
“…It is well known that production, viability and dispersal of powdery mildew conidia are affected by weather variables (e.g. surface wetness, wind speed) and host leaf age ( Ward & Manners, 1974; Butt, 1978; Butt & Jeger, 1986; Sivapalan, 1993a; Sivapalan, 1994; Xu et al ., 1995a ). However, to simplify the model, Podem TM does not take these effects into account.…”
Section: Details Of the Modelmentioning
confidence: 99%